2019
DOI: 10.1371/journal.ppat.1007690
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B e antigen induces the expansion of monocytic myeloid-derived suppressor cells to dampen T-cell function in chronic hepatitis B virus infection

Abstract: Chronic hepatitis B virus (HBV) infection is associated with functionally impaired virus-specific T cell responses. Although the myeloid-derived suppressor cells (MDSCs) are known to play a critical role in impairing antiviral T cell responses, viral factors responsible for the expansion of MDSCs in chronic hepatitis B (CHB) remain obscure. In order to elucidate the mechanism of monocytic MDSCs (mMDSCs) expansion and T cell function suppression during persistent HBV infection, we analyzed the circulation frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 40 publications
(58 reference statements)
3
61
0
Order By: Relevance
“…However, which cells in the spleen that are primarily responsible for HBeAg-increased TGF-β production requires further investigation. The present data suggest that HBV exploits immune cells to create an TGF-β-rich microenvironment for peripheral Treg differentiation and HBV persistence, and are consistent with the notion that HBeAg can condition innate immune cells into anti-inflammatory types (34,35).…”
Section: Discussionsupporting
confidence: 89%
“…However, which cells in the spleen that are primarily responsible for HBeAg-increased TGF-β production requires further investigation. The present data suggest that HBV exploits immune cells to create an TGF-β-rich microenvironment for peripheral Treg differentiation and HBV persistence, and are consistent with the notion that HBeAg can condition innate immune cells into anti-inflammatory types (34,35).…”
Section: Discussionsupporting
confidence: 89%
“…Although MDSCs have been reported to associate with protective functions in the context of acute liver inflammation, these cells seem to facilitate inflammation and tissue damage during chronic liver diseases. It was reported that HBV induces the expansion and activation of MDSCs [25], which favors T cell exhaustion. This leads to the establishment of persistent HBV infection and the maintenance of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine depletion leads to reduction of CD3ζ levels in T cells, subsequently causing TCR-pathway dysfunction (36). Intrahepatic inflammation recruits regulatory T cells (37-41), B cells, and myeloid-derived suppressor cells (42)(43)(44), and activate stellate cells, leading to IL-10 and TGF-β production (25). The suppressive events in the liver are vital for protection from severe damage primed by inflammation, while further impairing the functionality of HBV-specific T cells.…”
Section: Immune Pathogenesis Of Persistent Hbv Infectionmentioning
confidence: 99%